El desbarrancadero de Fernando Vallejo. Des/integración y cuidado en el cuerpo/corpus seropositivo latinoamericano (Altre Modernità, 2017)
In the following article, through Fernando Vallejo’s novel El desbarrancadero, I will reflect on the Latin American seropositive bodies; specifically the ones that experienced the disease at the end of the past century. In order to this I will analyze two concepts. First, the neologism des/integration, as a contemporary strategy to understand the body living with the disease, that seeks to find new forms of meaning and agency. And second, the concept of “caring for oneself”, which I intend to apply in the literary terrain, through self-writings (and readings), that enable innovative models of bioethical action to be applied with the purpose of understanding new and productive historicities for the Latin American region.